Flexible, stretchable, breathable and sweatproof all-nanofiber iontronic tactile sensor for continuous and comfortable knee joint motion monitoring. (1st December 2022) - Wang, Peng; Liu, Jun; Yu, Wei; Li, Guoxian; Meng, Chuizhou; Guo, Shijie
Abstract: Running improperly for an extended period of time will induce irreversible damage to knee joints, which can bring about excruciating pains to joggers. Wearable sensors for continual knee-monitoring are highly recommended. However, conventional flexible sensors built on airtight substrates are inferior in comfort when wearing for lengthy durations. Herein, a highly flexible and stretchable iontronic tactile sensor is developed on an electrospun thermoplastic polyurethane nanofiber platform. The multilayered, intertwined, nanofiber network housing numerous micro-pores/channels endows the sensor with superior air permeability, sweat inertness, thermal dissipation ability, and biocompatibility, which allows for an extended, comfortable wearing experience. Accrediting the supercapacitive sensing mechanism and porous microstructure, a performance exhibiting a high sensitivity, wide detection range, rapid response, excellent stability and repeatability can be achieved. Pragmatically, a knee-sensor prototype was developed and demonstrated running in real-time and continuously: monitoring a single point of pressure with 3 individual sensor units attached to the rim of the knee and mapping the spatial pressure distribution with an array of sensors covering the whole knee. The health status of the knee could be properly diagnosed, which would be useful for warning of potential knee injuries or to better the form of exercisers. Graphical Abstract: A flexible and stretchable iontronic tactile sensor is developed on an all-nanofiber platform. The sensor exhibits high sensing performance as well as air and moisture permeability and sweat inertness, which ensures a comfortable wearable sensing. Such sensor units and array tightly worn on the knee joint for single point and spatial distribution of pressure monitoring in a real-time and continuous manner is demonstrated. ga1 Highlights: A flexible and stretchable tactile sensor is fabricated on an electrospun all-nanofiber platform. Enhanced sensing performance is obtained due to supercapacitive sensing and porous microstructure. The nanofiber network also ensures breathability and sweatproof ability for a comfortable wearing. Characteristic pressure response waveforms of knee joint motion are obtained by sensor units. Mapping of pressure spatial distribution of knee joint motion is also acquired by sensor array.